1994
DOI: 10.1021/bi00205a025
|View full text |Cite
|
Sign up to set email alerts
|

Complex Molecular Mechanism for Dihydropyridine Binding to L-Type Ca2+-Channels As Revealed by Fluorescence Resonance Energy Transfer

Abstract: We analyzed binding-induced changes in the fluorescence properties of the 1,4-dihydropyridine (DHP), DMBODIPY-DHP [(-)-1,4-dihydro-2,6-dimethyl-4-(2-trifluromethylphenyl)- 3,5-pyridinedicarboxylic acid 2-[4,4-difluoro-5,7-dimethyl-4-bora-3a,4a-diaza-3- (s-indacene)propionylamino]ethylethyl ester)], to study the molecular mechanisms underlying the interaction of DHPs with the alpha 1-subunit of skeletal muscle L-type Ca2+ channels. The quantum yield of the fluorophore DMBODIPY was similar in solvents of differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 18 publications
1
28
1
Order By: Relevance
“…The presence of functional L-type Ca 2ϩ channels in DC is supported by three lines of evidence: (i) Ca 2ϩ -dependent DC functions, such as apoptotic body engulfment and IL-12 production, are inhibited by L-type Ca 2ϩ channel blockers; (ii) fluorescent DHP drugs, specific for the ␣1C chain of L-type channels (3,4), bind to DC surface; and (iii) the calcium channel ␤1 chain is detectable in DC lysates. In contrast, N-type calcium channels (1,25) In some experiments, Bay K 8644 10 M was added immediately prior apoptotic body challenge to untreated (light gray column) or Tat-pretreated cells (dark gray column).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The presence of functional L-type Ca 2ϩ channels in DC is supported by three lines of evidence: (i) Ca 2ϩ -dependent DC functions, such as apoptotic body engulfment and IL-12 production, are inhibited by L-type Ca 2ϩ channel blockers; (ii) fluorescent DHP drugs, specific for the ␣1C chain of L-type channels (3,4), bind to DC surface; and (iii) the calcium channel ␤1 chain is detectable in DC lysates. In contrast, N-type calcium channels (1,25) In some experiments, Bay K 8644 10 M was added immediately prior apoptotic body challenge to untreated (light gray column) or Tat-pretreated cells (dark gray column).…”
Section: Discussionmentioning
confidence: 96%
“…These channels are composed of three transmembrane subunits (␣1C, ␥, and the ␣2␦ complex) and one cytoplasmic chain (the ␤1 chain). A spectrum of compounds, the dihydropyridine (DHP) 1 derivatives, which specifically bind with high affinity to the ␣1C chain of L-type channels (3,4), regulating their functional state from blocking to opening, allows both the identification and the functional analysis of this class of molecules (1)(2)(3)(4). Cytosolic calcium rise is an important signal also in nonexcitable cells, including immune cells, regulating fundamental processes such as activation, growth, and differentiation (5)(6)(7).…”
mentioning
confidence: 99%
“…Most probably, the main reason for the latter discrepancy is the use of a non-equilibrium detection method (19), which could result in an artificially high dissociation constant for the labile complex. It was shown that filtration, being a nonequilibrium technique, tends to produce artifacts when rapid reactions and/or weak complexes are investigated (32)(33)(34)(35). Whereas the kinetics of mant-GDP binding to eRF3 was consistent with a one-step binding mechanism, the interaction of eRF3 with mant-GTP was more complex, and double-exponential time courses were indicative of a two-step binding process in which the initial association of mant-GTP and eRF3 is followed by a conformational change.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, guanine nucleotide exchange is traditionally evaluated using filtration-based assays requiring separation of bound versus free nucleotides, and previous relevant reports have used solidphase separation techniques to monitor exchange at single, arbitrary time points (24,25,27,28). Unfortunately, physical separation of solution components introduces the potential to perturb equilibrium conditions (50,51). In contrast, the studies described here rely upon the continuous, real time analysis of exchange activity using fluorescence spectroscopy and do not require altering the solution conditions in order to measure exchange.…”
Section: Discussionmentioning
confidence: 99%